2020
DOI: 10.3390/app10031138
|View full text |Cite
|
Sign up to set email alerts
|

Bending Resistance and Failure Type Evaluation of Basalt Fiber RPC Beam Affected by Notch and Interfacial Damage Using Acoustic Emission

Abstract: Generally, reactive powder concrete (RPC) contains steel fibers often exposed to aggressive environments. Steel fibers in such RPCs are subjected to corrosion in-service, which can significantly change the mechanical properties of the structural components. In this paper, basalt fibers were used to replace steel fibers for preparing a new basalt fiber modified reactive powder concrete (BFRPC). The bending resistance of BFRPC beams was studied, and the crack propagation and failure type of BFRPC beam were monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Owing to this, the microstructure of basalt fiber polymer-modified RPC materials is more compact and the mechanical properties, durability and toughness of basalt fiber polymer-modified RPC composites are improved. Therefore, basalt fiber polymer-modified RPC has the characteristics of ultra high strength, high durability and high temperature adaptability [ 8 , 9 , 10 ]. Basalt fiber polymer-modified RPC can effectively reduce the self-weight of structures and increase the spanning capacity, which has a broad application prospect in various infrastructure construction.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this, the microstructure of basalt fiber polymer-modified RPC materials is more compact and the mechanical properties, durability and toughness of basalt fiber polymer-modified RPC composites are improved. Therefore, basalt fiber polymer-modified RPC has the characteristics of ultra high strength, high durability and high temperature adaptability [ 8 , 9 , 10 ]. Basalt fiber polymer-modified RPC can effectively reduce the self-weight of structures and increase the spanning capacity, which has a broad application prospect in various infrastructure construction.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known that basalt fiber is produced from natural basalt material after melting at high temperatures, and as a new type of environmentally friendly and high-performance inorganic fiber material, basalt fiber has the advantages of high strength, low water absorption, acid and alkali resistance, high temperature resistance, and environmental protection [8][9][10][11]. Many researchers have carried out a large number of related experimental studies on basalt fiber-modified asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Grzeszczyk et al [29] evaluated the effect of basalt fiber content on the mechanical properties of RPC; their results showed that the flexural strength of RPC increased with the increase in basalt fiber content. Liu et al [30] reported that the basalt fiber could increase the toughness and bending strength of basalt fiber RPC beams, and improve the resistance to steel-concrete interface damage. Most research is about the mechanical properties of basalt fiber-reinforced reactive powder concrete.…”
Section: Introductionmentioning
confidence: 99%